Manajemen Strategis Sistem Informasi Menggunakan Metode The Open Group Architecture Framework (TOGAF) (Studi Kasus: SMA Galatia Bekasi) - Stevenius; Bororing, Grace Martha Geertruida (Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
Information systems in this era of globalization have a role in carrying out every activity in all fields. The use of computer technology and information systems is very helpful for humans in all jobs, especially in light and difficult jobs. Information systems strategy is a necessity that can help business organizations achieve the company's business goals. The Open Group Architecture Framework (TOGAF) is an architectural framework that provides methods and tools to assist the acceptance, production, use, and maintenance of Enterprise Architecture. Galatia High School located in Harapan Indah still uses a manual system to carry out their activities. Therefore, Strategic Management of Information Systems is needed to facilitate their activities and improve the quality of their services. This research was conducted by conducting direct observations and interviews with the Principal, Deputy Principal, and Administration. The interview results obtained were analyzed using the TOGAF technique. The author also uses literature studies from books, journals, and previous research. This research will produce an information strategy management system to increase the competitive value of Galatian High School and assist Galatian High School in realizing their vision.